2016
DOI: 10.5090/kjtcs.2016.49.4.232
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Neuroprotective Effect of Histidine-Tryptophan-Ketoglutarate Solution in an Ischemia/Reperfusion Spinal Cord Injury Animal Model

Abstract: BackgroundParaplegia is a devastating complication following operations on the thoracoabdominal aorta. We investigated whether histidine-tryptophan-ketoglutarate (HTK) solution could reduce the extent of ischemia/reperfusion (IR) spinal cord injuries in a rat model using a direct delivery method.MethodsTwenty-four Sprague-Dawley male rats were randomly divided into four groups. The sham group (n=6) underwent a sham operation, the IR group (n=6) underwent only an aortic occlusion, the saline infusion group (sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the quest of finding adjuncts to prevent spinal cord ischemic injury, a Japanese group has shown that CSF oxygenation with artificial CSF, using nanobubble technology, prevents spinal cord injury in a rabbit model [32]. A Korean group has shown the spinal cord protective effect of histidine-tryptophan-ketoglutarate (HTK) solution in a rat model [33]. Our group A animals showed higher degree of spinal protection as evidenced by clinical Tarlov scores, MEP parameters, and histopathology.…”
Section: Discussionmentioning
confidence: 72%
“…In the quest of finding adjuncts to prevent spinal cord ischemic injury, a Japanese group has shown that CSF oxygenation with artificial CSF, using nanobubble technology, prevents spinal cord injury in a rabbit model [32]. A Korean group has shown the spinal cord protective effect of histidine-tryptophan-ketoglutarate (HTK) solution in a rat model [33]. Our group A animals showed higher degree of spinal protection as evidenced by clinical Tarlov scores, MEP parameters, and histopathology.…”
Section: Discussionmentioning
confidence: 72%
“…16 HTK: HS and resuscitation, HTK administered intravenously at a constant rate. 17 ALO: HS and resuscitation, ALO at a 50 mg/kg dose. 18…”
Section: Study Groupsmentioning
confidence: 99%
“…In the last two years, many research studies, focusing on the identification of drugs potentially effective in SCI treatment, have been published [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Overview Of Current Pharmacological Approaches For the Trmentioning
confidence: 99%